Coordinated Portfolio investment Survey : Survey Guide. (International Monetary Fund, 1997)
This paper presents a coordinated portfolio investment survey guide provided to assist national compilers in the conduct of the Coordinated Portfolio Investment Survey, conducted under the auspices of the IMF with reference to the year-end 1997. The guide covers a variety of conceptual issues that a country must address when conducting a survey. It also covers the practical issues associated with preparing for a national survey. These include setting a timetable, taking account of the legal and confidentiality issues raised, developing a mailing list, and maintaining quality control checks.